Real-time erosion measurements of the HiVHAc and SPT-70 Hall thrusters via cavity ring-down spectroscopy - Lee, Brian Christopher, author; Lundeen, Stephen R., advisor; Yalin, Azer P., advisor; Roberts, Jacob L., committee member; Krueger, David A., committee member; Williams, John D., committee member (Colorado State University. Libraries, 2014)
Electric propulsion has moved to the forefront of in-space propulsion in recent years. By making exceptionally efficient use of propellant, electric propulsion devices have significantly reduced the cost of some missions and enabled others, which had not previously been possible. Among these devices, Hall thrusters have shown particular promise. However, for many thrusters of interest, sputter erosion of the insulating channel remains a problem and continues to limit the thruster lifetime. Diagnostic tools to assess the absolute channel erosion rate rapidly remain limited. This thesis describes the use of ultraviolet cavity ring-down spectroscopy (CRDS) as a real-time diagnostic of sputtered boron atoms in the thruster plume. Cavity ring-down spectroscopy is an ultra-sensitive laser-absorption technique which is particularly apt at measuring trace species number densities in the gas phase. In this work, ground-state atomic boron, which was sputtered from the thruster channel, was measured near 250 nm. The interrogating laser was swept across the exit plane of a Hall thruster, providing spatially-resolved boron number density measurements. Additionally, laser-induced fluorescence was used to measure the velocity of sputtered boron along the thruster axis, which were the first measurements of its kind. The measured boron number density and velocity component together provided a total boron flux from the thruster, and therefore, a channel erosion rate. Channel erosion rates of the NASA HiVHAc and the SPT-70 Hall thrusters were measured using CRDS. Absolute erosion rates and trends with operating condition were investigated. Both thrusters were found to erode at rates proportional to the discharge power, which is consistent with the available literature. Profilometry was also used to measure the channel erosion rate of the SPT-70 thruster and revealed a factor of ~5 disagreement with estimates made by CRDS. Calcium fluoride (CaF2) prism retroreflectors were developed, for the first time, as a means to improve both the bandwidth and finesse of optical cavities in the ultraviolet region. The CRDS technique used in thruster erosion measurements employed multilayer dielectric mirrors, which have relatively poor performance in the ultraviolet region. Calcium fluoride prism retroreflectors show promise to outperform the best available dieletric mirrors at 250 nm as well as provide broadband cavity operation. The design, construction, and characterization of the CaF2 prisms is presented.
Keywords: optical cavities; hall thrusters; plasmas; spectroscopy